2017
DOI: 10.3389/fmicb.2017.00282
|View full text |Cite
|
Sign up to set email alerts
|

Fish as Hosts of Vibrio cholerae

Abstract: Vibrio cholerae, the causative agent of pandemic cholera, is abundant in marine and freshwater environments. Copepods and chironomids are natural reservoirs of this species. However, the ways V. cholerae is globally disseminated are as yet unknown. Here we review the scientific literature that provides evidence for the possibility that some fish species may be reservoirs and vectors of V. cholerae. So far, V. cholerae has been isolated from 30 fish species (22 freshwater; 9 marine). V. cholerae O1 was reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 51 publications
2
91
5
Order By: Relevance
“…They therefore maintained that ornamental fish served as vectors of these microorganisms. Also Halpern and Izhaki () confirmed the role of marine and freshwater fish to disseminate these bacteria in the aquatic environments. Our results showed that there is no evidence as to whether any ornamental fish species is a better reservoir or vector of one of the two sister species compared to another, but it is clear that fish species originating from Asia were more likely to serve as vectors of field strains carrying virulence factors than the ones isolated during diagnostic testing.…”
Section: Discussionmentioning
confidence: 85%
“…They therefore maintained that ornamental fish served as vectors of these microorganisms. Also Halpern and Izhaki () confirmed the role of marine and freshwater fish to disseminate these bacteria in the aquatic environments. Our results showed that there is no evidence as to whether any ornamental fish species is a better reservoir or vector of one of the two sister species compared to another, but it is clear that fish species originating from Asia were more likely to serve as vectors of field strains carrying virulence factors than the ones isolated during diagnostic testing.…”
Section: Discussionmentioning
confidence: 85%
“…regarding a fish disease in the ponds next to where we collected the waterbirds. V. cholerae O1 and non-O1 have been isolated from different fish species (reviewed in [32]). V. cholerae and Aeromonas are inhabitants of fish and chironomids [4,18] consumed by waterbirds, which may be how V. cholerae and Aeromonas enter the waterbirds' intestine.…”
Section: Aeromonas Veroniimentioning
confidence: 99%
“…V. cholerae can form biofilms on chitinous substrates, such as the exoskeleton of crustaceans (8), and can colonize the gut of birds and fish, which may promote transmission in aquatic environments and perhaps contribute to human disease outbreaks (9,10). Within a human host, a complex set of signaling systems and external cues regulate colonization and disease factors, such as biofilm formation, chemotaxis-guided flagella, toxin-coregulated pili, several adhesins, and cell shape features, to ensure access of the microbe to the intestinal surface (11,12).…”
mentioning
confidence: 99%